Relationship between flash points of some binary base oils and their constituent oils - M. Shirani; A. Semnani; H. S. Langeroodi; H. Haddadi (Bulletin of the Chemical Society of Ethiopia, 2015)
Miscellaneous binary blends containing solvent neutral-150 (SN-150), solvent neutral-500 (SN-500), Bright Stock-150 (BS-150), polyalphaolephin-6 (PAO-6), PAO-100, a processed low sulfur waxy material, and polyisobutene-600 (PIB-600) were prepared and their corresponding flash point (FP) were measured. By using the measured FP data, the plots of FP vs. weight percentage of minor component were drawn and the equations due to each plot were derived. Except PIB-600 containing mixtures, linear relation between FP of blends and weight percentage of constituents has been observed. Also the obtained data indicate that except PIB-600 containing blends the FP of such mixtures can be calculated from the summation of "FP × weight ratio" of each component. In the case of PIB-600 containing blends, nonlinear and decreasing, nonlinear and increasing were observed as well as constant trends of FP vs. weight percentage of minor component. The observations have been interpreted based on the composition, molecular weight, and interactions of the constituents of the base oils.